An Exuberant Case of Ulceronodular-Rupioid (Malignant) Syphilis in an HIV Patient: A Proposal for New Diagnostic Criteria - Dennys Jimenez; Marian Santillan Rabe; Apeksha N. Agarwal; Scott R. Dalton; Gregory M. Anstead (MDPI AG, 2024)
We report the case of a 28-year-old male with uncontrolled human immunodeficiency virus (HIV) infection who presented with extensive ulcerated lesions with dark lamellated crusting on his face, torso, and limbs. The patient had a rapid plasma reagin (RPR) titer of 1:512, indicative of syphilis. A skin biopsy revealed granulomata surrounded by lymphocytes, histiocytes, and plasma cells, with spirochetes visible on immunohistochemical staining. The patient's rash resolved with hyperpigmented scarring after penicillin and doxycycline treatment. This severe form of secondary syphilis has been termed malignant syphilis, lues maligna, ulceronodular syphilis, or rupioid syphilis. We propose a single descriptive name for this entity, ulceronodular-rupioid syphilis. In 1969, Fisher proposed criteria for malignant syphilis based on lesion appearance, histopathologic findings, high RPR values, and rapid response to treatment. We found that the Fisher criteria were imprecise with respect to specific histopathologic findings, the quantitation of RPR values, and what constitutes rapid response to treatment. Thus, we examined an additional 74 cases from the literature and propose new diagnostic criteria based on rash appearance, histopathologic characteristics, non-treponemal and treponemal test positivity, and response to therapy. We also found that uncontrolled viremia, and not a low CD4 count, is a major risk factor for ulceronodular-rupioid syphilis in HIV patients.